Diversity of growth performance and rumen microbiota vary with feed types - Du, Shuai; Bu, Zhenkun; You, Sihan; Bao, Jian; Jia, Yushan (Frontiers in Sustainable Food Systems, 2022)
Diet is a major factor in influencing the growth performance and the microbial community of lambs. This study aimed to investigate how diverse diets influence their growth performance and rumen microbiota. Ninety male lambs were randomly allocated into three groups in a completely randomized design with equal lambs: non-pelleted native grass hay (HA) as the control diet and pelleted native grass hay (GP) and pelleted native grass hay with concentrate (GPC) as experimental diets. The rumen fluid samples of the lambs in the HA, GP, and GPC groups were used to study rumen microbiota diversity through 16S rDNA high-throughput sequencing. In the present study, the final body weight, dry matter intake, and average daily gain differed significantly (p < 0.05) among the HA, GP, and GPC groups. Compared to the HA group, higher final body weight, dry matter intake, and average daily gain were found in the GP group. Similarly, better animal performance was observed in the GPC group than in the GP group. The principal coordinates analysis displayed that the composition of the rumen microbiota in the three groups was distinctly separated from each other. Bacteroidetes and Firmicutes were the dominant members of the community in the HA and GP groups, while Bacteroidetes, Firmicutes, and Proteobacteria became the predominant members in the GPC group. The comparison among these groups showed significant (p < 0.05) differences in Rikenellaceae_RC9_gut_group, Prevotella_1, Ruminococcaceae_NK4A214_group, and Succiniclasticum. These results suggest that the GP and GPC diets are more beneficial for growth performance than the HA diet and also indicate that the rumen microbiota varied in response to different feed types. In conclusion, these results could provide strategies to influence rumen microbiota for better growth and a healthier ecosystem on the Mongolian Plateau and lay the theoretical groundwork for feeding the pelleted native grass diet.